Graves’ Disease Presenting with Complete Atrioventricular Block - Young Sil Eom; Pyung Chun Oh (Case Reports in Endocrinology)
Hyperthyroidism commonly causes tachyarrhythmias such as sinus tachycardia and atrial fibrillation. Impaired atrioventricular conduction is a very rare complication of hyperthyroidism. We report a case of a patient with hyperthyroidism due to Graves’ disease presenting with syncope and complete atrioventricular block. Because lack of awareness of atypical presentation in patients with hyperthyroidism may delay diagnosis and treatment, the recognition that hyperthyroidism can be one of the reversible causes of complete atrioventricular block is important.